Preoccupying Zones: The Young Artist of the Year 2004- The Hassan Hourani Award- A.M. Qattan Foundation/ (3CafjI TGZdI(B: (3eSGHbI GdafGf GdTGH ddYGe (B2004- (3LGFRI MSf GdMhQGfj(B- (3eDSSI YHO GdeMSf GdbWGfs - Craddock, Sacha (3SGTG cQGOhcs; Mahmoud AbuHashhash (3CHhgTT, eMehOs; Hassan Hourani Award (London/Ramallah; A.M. Qattan Foundation, 2006)
Exhibition catalog. Curator: Khalil Rabah; Editor: Mahmoud Abu Hashhash. Exhibitions @ A.M. Qattan Foundation; Khalil Sakakini Cultural Centre; Al Hallaj Gallery- League of Palestinian Artists and the Ottoman Court (Ramallah); Friends Boys School (Al-Bireh). Jury: Okwui Enwezor, Hosni Radwan, Sacha Craddock, Suad AlAmiri, Sharif Waked. Essays: Omar Al Qattan, Mahmoud Abu Hashhash, Sacha Craddock. Artists: Mohannad Yaqoubi, Mohammed Musallam, Sohail Salem, Steve Sabella, Shadi AlZaqzouq, Alexandra Handal, Shuruq Harb, Shadi HabibAllah, Mohammad Joha, Mohamed AbuSall.
English; Arabic
Keywords: 21st century; NX411-415 Arts in general- Competitions; Palestine